Oxygen‐Promoted Suzuki–Miyaura Reaction for Efficient Construction of Biaryls. Issue 1 (13th November 2015) - Liu, Chun; Li, Xinmin
Abstract: As one of the most powerful and versatile methods for the construction of carbon–carbon bonds, the Suzuki–Miyaura cross‐coupling reaction has attracted great attention over the past three decades. In recent years, a huge amount of interest has been focused on the development of ligand‐free Suzuki–Miyaura reaction systems, which have the advantages of low cost, mild reaction conditions, and easy operation. So far, a number of ligand‐free Suzuki–Miyaura reaction systems have been developed by using simple palladium salts, nanopalladium, or supported palladium catalysts. In this account, we will review our recent research on the oxygen‐promoted ligand‐free Suzuki–Miyaura reaction. Interestingly, the oxygen‐promoting effect has been observed in different reaction media, including polyethylene glycol, organic/water mixed solvents and pure water. The oxygen‐promoted reaction systems demonstrate high efficiency for the construction of biaryls. Abstract : Ligand‐free Suzuki–Miyaura reaction systems have recently attracted huge interest. In this account, we will review our recent research on the oxygen‐promoted ligand‐free Suzuki–Miyaura reaction. The oxygen‐promoting effect has been observed in various reaction media, including polyethylene glycol, organic/water mixed solvents and pure water.